2009
DOI: 10.1521/aeap.2009.21.2.169
|View full text |Cite
|
Sign up to set email alerts
|

“If You Don't Abstain, You Will Die of AIDS”: AIDS Education in Kenyan Public Schools

Abstract: We explored constraints of implementing AIDS education in public schools in Kenya. Sixty interviews with teachers and 60 focus group discussions with students were conducted in 21 primary and nine secondary schools. System/school-level constraints included lack of time in the curriculum, limited reach of secondary-school students (because AIDS education is embedded in biology, which is not compulsory), and disapproval of openness about sex and condoms by the Ministry of Education and parents. Alternative strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 5 publications
7
18
1
Order By: Relevance
“…Furthermore this study suggests that the school influenced how all students were socialized into maintaining stigmatizing beliefs about HIV due to a clear lack of scientific information in the school curriculum demythologizing HIV. This study confirms published findings that educators lack proper training regarding HIV and at times breached students’ confidentiality regarding their HIV status [ 18 , 20 , 35 , 36 ]. However, this study takes this concept a step further by suggesting that the school environment itself in Kisumu influenced LTFU among YLWH.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore this study suggests that the school influenced how all students were socialized into maintaining stigmatizing beliefs about HIV due to a clear lack of scientific information in the school curriculum demythologizing HIV. This study confirms published findings that educators lack proper training regarding HIV and at times breached students’ confidentiality regarding their HIV status [ 18 , 20 , 35 , 36 ]. However, this study takes this concept a step further by suggesting that the school environment itself in Kisumu influenced LTFU among YLWH.…”
Section: Discussionsupporting
confidence: 91%
“…However, this study takes this concept a step further by suggesting that the school environment itself in Kisumu influenced LTFU among YLWH. Despite the fact that the majority of participants in this study believed support was impossible without disclosure, support can be provided to YLWH by creating a welcoming environment free of stigma [ 35 , 36 ]. If the environment is not supportive, youth and families cannot be expected to be forthcoming in their disclosures.…”
Section: Discussionmentioning
confidence: 99%
“…In some other contexts, programme implementation of a computer-led programme has been strongly hampered by non-availability and lack of access to electricity and to the Internet. These findings are in line with many other studies conducted on sexuality education in Sub-Saharan Africa (Ahmed et al 2009;kinsman, Harrison, and kengeya-kayondo 1999;Njue et al 2009), which identified a lack of relevant resources as major barriers of implementation. A lack of motivation among teachers who provided sexuality education after school hours has also been noted when they do not receive financial compensation for their extra work.…”
Section: Programme Fidelitysupporting
confidence: 90%
“…It is predominantly an HIV/AIDS prevention curriculum with one dedicated HIV/AIDS lesson each week incorporated into standard teaching. Most of the HIV/AIDS teaching in this program is factual, but according to Njue, Nzioka, Ahlberg, Pertet, and Voeten (2009), the program does not fully address psychosocial issues required by a prevention curriculum and gives conflicting messages on contraceptives and condom use. According to the researchers, when primary school teachers received training on the curriculum, Ministry of Education officials urged them not to discuss contraceptives and condom use with students, although these topics are contained in the curriculum.…”
Section: Resultsmentioning
confidence: 99%